(untitled) (Palíndromo, 2017)
This study intends to approach the artistic trajectory and aesthetic production of Eder Santos, privileging the works that have the video as one of the supports. With a multifaceted production and trajectory, as videomaker, filmmaker, publicity and artist, this analysis privileges its produc-tion in this last undertaking. Starting with its participation with single channel videos in video festivals, in particular Videobrasil, we will soon go through its internationa-lization, demonstrating some participation in festivals and art shows in foreign mu-seums, until concluding with the creation of video installations that served to insert the artist in the emerging circuit of tradi-tional arts here in Brasil, at a time of new perspectives and fruitful expansion of the world of contemporary art. Moreover, the aesthetic analyzes of the works of Santos in this study privilege the theme of the po-litics of memory, which has as a recurrent historical rescue to the past, in which we try to present possible axes of reading un-der this conception.